2005
DOI: 10.1002/esp.1181
|View full text |Cite
|
Sign up to set email alerts
|

The role of vegetation patterns in structuring runoff and sediment fluxes in drylands

Abstract: The dynamics of vegetation-driven spatial heterogeneity (VDSH) and its function in structuring runoff and sediment fluxes have received increased attention from both geomorphological and ecological perspectives, particularly in arid regions with sparse vegetation cover. This paper reviews the recent findings in this area obtained from field evidence and numerical simulation experiments, and outlines their implications for soil erosion assessment. VDSH is often observed at two scales, individual plant clumps an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
318
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(338 citation statements)
references
References 82 publications
12
318
0
8
Order By: Relevance
“…Differences in soil environments, and water runoff and soil loss production capacity for bare and plant-covered surfaces increased the heterogeneity of sources and sinks of soil material and runoff water (Imeson and Prinsen, 2004;Puigdefabregas, 2005). These heterogeneous patterns are very important in controlling water runoff and soil loss (Rey, 2004), and some research (Valentin et al, 1999;Martínez Raya et al, 2006) documented the banded or stripped pattern of vegetation would reduce much more water runoff and increase productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in soil environments, and water runoff and soil loss production capacity for bare and plant-covered surfaces increased the heterogeneity of sources and sinks of soil material and runoff water (Imeson and Prinsen, 2004;Puigdefabregas, 2005). These heterogeneous patterns are very important in controlling water runoff and soil loss (Rey, 2004), and some research (Valentin et al, 1999;Martínez Raya et al, 2006) documented the banded or stripped pattern of vegetation would reduce much more water runoff and increase productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested that the size of the bare patches between plants is the dominant factor determining the production of runoff at plot scale (Lavee et al, 1998), relating this fact to the connectivity of fluxes within the system (Puigdefábregas, 2005). Accordingly, the closer the bare and crusted areas from the outlet of the plot, the higher the soil loss.…”
Section: Differences In Soil Loss Derived From Replicate Soil Erosionmentioning
confidence: 99%
“…This makes hydrological studies difficult in these areas (Heydarpour, 1989). Runoff is a fundamental process because it leads to water redistribution, and it modulates soil water availability and plant functioning (Huxman et al, 2004;Lázaro, 2004;Sánchez and Puigdefábre-gas, 1994), especially in semiarid environments (Aguiar and Sala, 1999;Calvo-Cases et al, 2003;Porporato et al, 2002;Puigdefábregas, 2005); and is highly dependent on rainfall.…”
Section: Introductionmentioning
confidence: 99%